Extraction-Spectrophotometric Determination of Bismuth(III) in Wood´ s Alloy through Complexation of Hexaiodobismuthate and Prochloroperazine Mesylate - Somasekharappa, K.G.; Ramappa, P.G. (Asian Journal of Chemistry, 2010)
A new modified spectrophotometric method for the determination of trace quantities of bismuth has been developed based on the complexation between prochlorperazine mesylate and hexaiodobismuthate. The orange-red complex, which is stable for 48 h has an absorption maxima at 485 nm with a molar absorptivity of 3.53 x 103 L per mol per cm and Sandall's sensitivity 0.16 μg cm–2. Calibration graph is rectilinear for 0.6 to 18 ppm of bismuth. Effect of time, temperature, reagent concentration and order of addition of reagents have been studied. The proposed method had been used for the determination of bismuth in Wood's alloy as it offers the advantages of simplicity, rapidity and accurate procedure.